2015
DOI: 10.1016/j.nano.2014.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Liposome-based mucus-penetrating particles (MPP) for mucosal theranostics: Demonstration of diamagnetic chemical exchange saturation transfer (diaCEST) magnetic resonance imaging (MRI)

Abstract: Mucus barriers lining mucosal epithelia reduce the effectiveness of nanocarrier-based mucosal drug delivery and imaging (“theranostics”). Here, we describe liposome-based mucus-penetrating particles (MPP) capable of loading hydrophilic agents, e.g., the diaCEST MRI contrast agent barbituric acid (BA). We observed that polyethylene glycol (PEG)-coated liposomes containing ≥7 mol% PEG diffused only ~10-fold slower in human cervicovaginal mucus (CVM) compared to their theoretical speeds in water. 7 mol%-PEG lipos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 20 publications
1
38
0
1
Order By: Relevance
“…The presence of PEG on the liposome surface can prevent aggregation of liposomes, though incorporating too much PEG can compromise liposome formation and stability. Yu and coworkers reported that when the PEG-lipid conjugate content was increased to 12 mol%, both the drug loading and in vivo vaginal distribution was reduced [139]. …”
Section: Methods For Nanoparticle Pegylation and Quantification Ofmentioning
confidence: 99%
See 3 more Smart Citations
“…The presence of PEG on the liposome surface can prevent aggregation of liposomes, though incorporating too much PEG can compromise liposome formation and stability. Yu and coworkers reported that when the PEG-lipid conjugate content was increased to 12 mol%, both the drug loading and in vivo vaginal distribution was reduced [139]. …”
Section: Methods For Nanoparticle Pegylation and Quantification Ofmentioning
confidence: 99%
“…Yu and coworkers prepared liposomes composed of standard neutrally charged lipids (DSPC), cholesterol, and different amounts of lipids conjugated to 2 kDa PEG (DSPE-PEG 2k ) to produce liposomes with a range of PEG surface densities [139]. They found that the non-PEGylated liposome formulation was relatively polydisperse and showed some signs of aggregation, whereas the PEGylated liposomes were relatively uniform in size, highlighting the added stability provided by PEG coatings.…”
Section: Non-systemic Applications For Improved Delivery With Pegymentioning
confidence: 99%
See 2 more Smart Citations
“…As a result of the interest in developing agents for detection on 3 T and lower field scanners, recent studies have emphasized the design of compounds with chemical shifts from water (Δω) > 4 ppm (27). Based on this criteria, barbituric acid (28,29), thymidine analogs (30), iodinated compounds (31-33), imidazoles (34) salicylic acid and anthranilic acid analogs have come to the forefront. The salicylates and anthranillates are particularly appealing based on their chemical structure consisting of a phenol proton hydrogen bonded to a carboxylate, which has been known with large chemical shift (35-37) which is particularly favorable for 3 T scanners based on their Δω = 6 -12 ppm and the capability of tuning k ex from 400 - 3000 s −1 , suitable rates for detection of CEST contrast.…”
Section: Small Molecule Cest Probesmentioning
confidence: 99%